EFFORT ESTIMATION MODELING OF E-GOVERNMENT APPLICATION DEVELOPMENT USING FUNCTION POINTS BASED ON TOR AND SRS DOCUMENT - Noorlela Marcheta; Irman Hermadi; Yani Nurhadryani (Journal of Information Technology and Its Utilization, 2020)
Software cost estimation is important for information systems management and is generally taught in software engineering courses especially to terms of the ever-increasing development of E-Government. A significant challenge for Software Sizing (SS) is to determine cost estimates based on TOR documents that do not yet contain complete Software Requirements Specifications (SRS). This study uses Function Points as one of the measurement methods that can make cost estimates and expert needs based on the desired functional system. On the other hand, there are cases where estimation needs after the SRS document have been made. Thus in this study, the authors discuss the implementation of SS based on TOR and SRS documents for E-Government. The results of this study indicate the closeness of the actual and estimated values of 81.9% for TOR and 93.4% for SRS.